Multidimensional Assessment of Athletic and Non-Athletic Female Students Through Analysis of BMI, Body Perception, Objectification, and Attitudes Towards the Ideal Body - Badau Dana; Badau Adela; Teodor Dragos Florin; Dinciu Corina Claudia; Dulceata Victor; Manescu Dan Cristian; Manescu Catalin Octavian; Litoi Florin Marin; Stoica Alina- Mihaela (Behavioral Sciences, 2025)
This study critically examines the multidimensional differences in body image perceptions among female students who participate in regular sports activities compared to their sedentary counterparts. The investigation involved a sample of 436 female students divided into two distinct groups: the sports group (GS, n = 180), consisting of participants from physical education and sports disciplines, and the non-sports group (GNS, n = 256). Anthropometric measurements such as height, weight, and body mass index (BMI) were systematically taken, along with the administration of three validated psychometric tools: the Silhouette Rating Scale (SRS) to assess body perception and satisfaction, the Objectified Body Consciousness Scale (OBC) to evaluate body objectification, and the Ideal Body Stereotype Scale-Revised (IBIS-R) to analyze perceptions of ideal body stereotypes. Notably, body dissatisfaction (SRS-D) showed the strongest correlation with BMI in both groups, with the non-athletic group displaying slightly higher correlation coefficients (r = 0.940) compared to the athletic group (r = 0.904; p < 0.001). Additionally, stereotypes related to the ideal body (IBIS-R) were strongly correlated with BMI in the non-athletic group (r = 0.846), whereas the athletic group showed a slightly lower correlation (r = 0.805). The body objectification measure (OBC) demonstrated moderate correlations, with the non-athletic group showing stronger associations (r = 0.394 vs. r = 0.352). Linear regression analysis revealed that non-athletic individuals exhibited higher predictive validity, characterized by greater R2 values and stronger correlations between physical and psychosocial factors. The results indicate that participation in sports serves as a protective factor against negative body image, shown by weaker correlations in the sports group. This research suggests that engaging in physical activities is associated with healthier body profiles and a more positive body image, leading to greater satisfaction and more realistic perceptions of body size.
Keywords: body image perception; objectified body consciousness; body size; body dissatisfaction; body stereotypes